What is the value of a Premier League football club to a regional economy?. Issue 5 (19th October 2016) - Roberts, Annette; Roche, Neil; Jones, Calvin; Munday, Max
ABSTRACT: Research question: This paper focuses on estimating the net regional economic impact of a UK Premier League football club. The drivers of local economic effects, factors constraining impacts, and the return on public investment for peripheral regions are considered. Research methods: Financial information from a UK Premier League team (Swansea City Football Club) and a spectator spending survey are used. The wider regional economic effects are assessed using a bespoke Input–Output model of the Welsh economy, incorporating a tourism satellite account. Results and findings: The net regional economic impact of Swansea City Football Club was estimated at £46 m of gross value-added and 216 jobs. Game attendee spending impacts are estimated to be close to zero once the spending of Swansea City Football Club fans at away matches outside the region is considered. The substantial broadcast television income is an important a source of external financial flows to the home region. Implications: This paper adds to the evidence base on the economic impacts of regular season-based sport in peripheral regions. The research identified a substantial return on the public investment in the stadium infrastructure due to the redistribution of significant Premier League television revenues to the regional economy.